Endoscopic ultrasound-guided ablation of pancreatic cystic lesions - Jin Ho Choi; Sang Hyub Lee (Society of Gastrointestinal Intervention, 2022)
Endoscopic ultrasound (EUS)-guided ablation procedures are emerging as minimally invasive therapeutic methods that address unmet needs in treatment methods for pancreatic cystic lesions (PCLs). Several studies have been published on the feasibility and efficacy of EUS-guided chemical ablation for PCLs, but further research on the actual treatment effects and real clinical benefits is needed. EUS-guided radiofrequency ablation for PCLs has recently been introduced. This review aimed to describe the broad framework of EUS-guided ablation treatments for PCLs and to present a blueprint for the future of these treatment methods.